The effectiveness of Carie-Care™, chemomechanical caries removal technique in primary teeth: randomized controlled clinical trial - Alaa Y. Ghanem; Dalia M. Talaat; Marwa M. Essawy; Niveen Bakry (BMC, 2023)
Abstract Background Chemomechanical techniques for caries removal have been introduced to overcome the shortcomings of the conventional rotatory instruments. This study aimed to clinically evaluate the effectiveness of the chemomechanical method of caries removal (Carie-Care™) over mechanical caries removal through the Atraumatic Restorative Technique in pediatric patients. Methods A randomized controlled clinical trial was conducted. Fifty children fulfilling inclusion criteria were recruited from the outpatient clinic of Pediatric and Dental Public health department, Faculty of Dentistry, Alexandria University. Fifty open carious primary molars were randomly assigned into 2 equal groups according to the method of caries removal. In Group I (test group), caries was removed using the Carie-Care™ system and in Group II (control group), by using mechanical caries removal through the atraumatic restorative technique. Resin modified glass ionomer was used for teeth restoration, the two techniques were compared in each child according to time taken for caries removal, efficacy of caries removal, pain assessment, and child behavior. Results The mean time taken for caries removal in the Carie-Care™ treatment group was (575.6 ± 114.8) seconds which was statistically significant higher as compared with the ART treatment group (346.1 ± 97.4) seconds (p < 0.001). The mean score of efficacy in caries removal was (0.6 ± 0.8) in the Carie-Care™ group, and (1.3 ± 0.7) in the ART treatment group. When compared to ART, Carie-Care™ was significantly more efficient in caries removal (p < 0.002). When pain was assessed by the SEM scale, it was observed that the Carie-Care™ caries removal technique showed statistically significantly more comfort during the procedure compared with the ART procedure (p < 0.001).Moreover, children in the Carie-Care™ group enjoyed the process and showed more cooperative behavior when assessed at the end of procedure than those in the ART group with statistically significant difference (p = 0.002). Conclusions Removal of carious tissue in primary teeth using Chemomechanical Carie-Care™ gel proved to be more time consuming than ART, but on the other hand it was more efficient, comfortable, and accepted by the pediatric patients.